Analisis Pengaruh E-Commerce, Budaya Organisasi, dan Penggunaan Sistem Informasi Akuntansi terhadap Kinerja Keuangan pada Usaha Mikro Kecil dan Menengah (UMKM) di Kota Kediri Tahun 2024 - Nurrenza Azizah; Erna Puspita; Diah Nurdiwaty (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2025)
This study discusses the importance of Micro, Small and Medium Enterprises (MSMEs) in improving the economy in Indonesia, but MSMEs often face challenges in improving financial performance in the digital era. Digitalization through e-commerce, a strong organizational culture, and the use of accounting information systems are key factors in improving the financial performance of MSMEs. This study aims to analyze the influence of e-commerce, organizational culture, and the use of accounting information systems on financial performance in MSMEs in Kediri City, as well as provide recommendations for MSME actors to improve financial performance. This study uses a quantitative approach with a sampling technique using the slovin formula with a sample of 100 respondents, namely MSME actors registered at DINKOP UMTK Kediri City, and data is collected through questionnaires. The analysis techniques used are validity test, reliability test, classical assumption test, multiple linear regression test, determinant coefficient test, t test, and F test.